Seeds in rocky soil: the interactive role of entrepreneurial legacy and bridging in family firms' organizational ambidexterity - Rolf Wilmes; Leif Brändle; Andreas Kuckertz (Small Business Economics, 2023)
Existing research on family firms emphasizes the importance of entrepreneurship across generations but leaves the role of entrepreneurial transmissions between predecessors and successors relatively unexplore . Building on the concept of entrepreneurial legacy, we ask how interactions of entrepreneurial mindsets and resources influence organizational ambidexterity in family firms. The study's central argument (and metaphor) is that organizational ambidexterity thrives in multigenerational family firms if successors' awareness of the family's entrepreneurial legacy (the right seed) interacts with predecessors' provision of entrepreneurial resources during succession (the fertile soil), also known as entrepreneurial bridging. We analyze a unique sample of successors from 296 multigenerational family firms in the agricultural sector. Our results point to the relevance of entrepreneurial resources in predecessor-successor collaborations to unlock the family firm's ability to balance entrepreneurial exploration and exploitation.
Keywords: C12; C83; D22; L26; O30; Q16; 330; Family firm; Entrepreneurial legacy; Succession; Transgenerational entrepreneurship; Organizational ambidexterity